1978
DOI: 10.1007/bf00996654
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features of the plasma cells in ?non-secretory? myeloma

Abstract: A case of "non-secretory" multiple myeloma is described. The diagnosis was based on the clinical picture, typical radiological findings, and infiltration of the bone marrow by myeloma cells which showed specific immunofluorescence staining mainly with antisera for IgM and kappa light chains. An attempt is made to explain the absence of pathological proteins in the serum, based on the ultrastructural findings of the myeloma cells, which showed "buddings" of the cell membranes containing endoplasmic reticulum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

1981
1981
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…The protein abnormalities in patients with plasma cell leukemia are similar to those of classic myeloma [9j, although in cases with poorly differentiated cells they could produce little or no paraprotein [2], The internal ultrastructure of the imma ture plasma cells of this patient, in both bone marrow and peripheral blood, was similar to that described in a previous case of nonsecretory myeloma [8], except for the absence of membranal protrusions and the scanty amount of endoplasmic reticulum, findings which may be related to the nonse cretory behavior of the cells. The presence of microfilaments located mainly in the vi cinity of the nuclear invagination is a rare finding in myeloma cells and most probably indicates the immature state of the neoplas tic cells.…”
Section: Discussionsupporting
confidence: 72%
“…The protein abnormalities in patients with plasma cell leukemia are similar to those of classic myeloma [9j, although in cases with poorly differentiated cells they could produce little or no paraprotein [2], The internal ultrastructure of the imma ture plasma cells of this patient, in both bone marrow and peripheral blood, was similar to that described in a previous case of nonsecretory myeloma [8], except for the absence of membranal protrusions and the scanty amount of endoplasmic reticulum, findings which may be related to the nonse cretory behavior of the cells. The presence of microfilaments located mainly in the vi cinity of the nuclear invagination is a rare finding in myeloma cells and most probably indicates the immature state of the neoplas tic cells.…”
Section: Discussionsupporting
confidence: 72%
“…Since they contained cytoplasmic material, including endoplasmic reticulum, it is conceivable that they posses also pathological proteins which leak through the surrounding membranes. This assumption is sup ported by the observation that in one case with non-secretory multiple myeloma the cellular 'buddings' could not be detected with the TEM [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may account for such a false nonsecretion. In one case, "buddings" of the cell membranes contained cytoplasmic and endoplasmic reticulum (ER) materials and were postulated to excrete Ig within vesicles that therefore could not be detected in serum as soluble proteins [21]. In several other cases, although monoclonal Ig were absent from serum and urines, kidney nonamyloid (Randalltype) deposits or myeloma casts clearly pointed to the accumulation of a monoclonal Ig at a distance from the proliferating cells, and in one case, studies at the molecular level confirmed that myeloma cells were producing the very same glycosylated monoclonal V IV LC, which was identified within kidney deposits [20,22].…”
Section: Nonsecretory Myeloma: a Rare Entity Still Getting Rarermentioning
confidence: 99%